2013
DOI: 10.1007/s13187-013-0488-7
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of a Community-Based Breast Cancer Education Intervention in the New York State Capital Region

Abstract: Objectives We determined the effectiveness of a community-based breast cancer education intervention among understudied populations in the New York State (NYS) Capital Region by assessing and comparing baseline and post-education breast cancer knowledge. Methods Participants included 417 students recruited from five colleges/universities and 67 women from four community group organizations. Baseline and post-education knowledge was assessed via self-administered mostly multiple-choice questionnaires. An open… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 24 publications
8
9
0
Order By: Relevance
“…The results of the present study agreed with the findings by Açıkgöz et al (32) and Ceber and colleagues in Turkey (22). The results of this study were similar to studies conducted in western Kenya, in Jordan, in the New York State Capital Region, in Taiwan, in studies conducted with immigrant Latino women and in Egypt and they revealed that there was a highly significant improvement in all knowledge items delivered to the intervention group from the pre to the post-test (6,27,(33)(34)(35)(36). As can be understood from the results of the above previous studies, training is the best way to increase knowledge.…”
Section: Discussionsupporting
confidence: 91%
“…The results of the present study agreed with the findings by Açıkgöz et al (32) and Ceber and colleagues in Turkey (22). The results of this study were similar to studies conducted in western Kenya, in Jordan, in the New York State Capital Region, in Taiwan, in studies conducted with immigrant Latino women and in Egypt and they revealed that there was a highly significant improvement in all knowledge items delivered to the intervention group from the pre to the post-test (6,27,(33)(34)(35)(36). As can be understood from the results of the above previous studies, training is the best way to increase knowledge.…”
Section: Discussionsupporting
confidence: 91%
“…However, the posttest of the present study demonstrated significant improvements in students' performance of BSE, which is certainly attributed to the practical part of the program. The effectiveness of the program in improving the practice of BSE is in agreement with a number of studies from several countries as in China (Ouyang and Hu, 2014), Ghana (Mena et al, 2014), the United States (Zeinomar and Moslehi, 2013) as well as in Alexandria, Egypt (Kharboush et al, 2011). …”
Section: Discussionsupporting
confidence: 85%
“…14,20,21 The educational intervention resulted in significant improvement in all the BC knowledge domains. Our findings concur with the results of other BC educational interventions undertaken in different international studies conducted in United States, 17 United Kingdom, 18 Colombia, 16 Egypt, 23 Iran 24 and Kenya. 25 Awareness of BC risk factors improved significantly after the educational intervention.…”
Section: Discussionsupporting
confidence: 91%
“…14,15 Educational interventions have proven to be effective in increasing the knowledge of BC and practice of breast self-examination. [16][17][18][19] Very few studies have been conducted in UAE assessing the knowledge of BC and its screening in the Arab women. 14,20,21 These studies reported lack of awareness regarding BC among these women and emphasized on the urgent need of community educational interventions to raise the awareness and knowledge of BC and its screening procedures.…”
Section: Introductionmentioning
confidence: 99%